1971
DOI: 10.1128/mmbr.35.2.206-227.1971
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmas and cell cultures.

Abstract: Such terms are now in disfavor and the correct generic name, Mycoplasma, should be used. Recently the mycoplasmas have been classified into two separate families, the sterol-requiring Mycoplasmataceae and the sterol-nonrequiring Acholeplasmataceae (44). To the present time, over 30 named species of mycoplasmas have been included within the two families. In addition there are several unidentifiable isolates (L. Hayflick, personal communication). The above classification refers to classic (large-colony) mycoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(32 citation statements)
references
References 128 publications
1
31
0
Order By: Relevance
“…The significance of the interactions between mycoplasmas and mammalian cells has only recently begun to be realized. Current knowledge on this subject was recently reviewed by Stanbridge (23). A number of investigations have shown that certain mycoplasma species are capable of adsorbing to the surfaces of animal cells (14,17,18,19,24,27).…”
mentioning
confidence: 99%
“…The significance of the interactions between mycoplasmas and mammalian cells has only recently begun to be realized. Current knowledge on this subject was recently reviewed by Stanbridge (23). A number of investigations have shown that certain mycoplasma species are capable of adsorbing to the surfaces of animal cells (14,17,18,19,24,27).…”
mentioning
confidence: 99%
“…Surprisingly, the antisera immunoprecipitated apparently identical surface proteins from the SV4O-transformed human cell line, SV80. Although the surface proteins detected by our antisera may be well-conserved cellular proteins, the possibility exists that at least some of these proteins could be of retroviral (Tung et al, 1976;Klitzman et al, 1980) or mycoplasma origin (Stanbridge, 1971 ; Vennegoor et d., 1982).…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that diamines other than putrescine may also inhibit mycoplasma proliferation. Considering the diverse impact of mycoplasma infection i n vitro (Stanbridge, 1971;McGarrity et al, 1978) 'Note added in proof Alhonen-Hongisto, L., Veijalainen, P., EK- and in vivo (Sharp, 19701, this possibility warrants further investigation. Ham (1965) originally found that exogenous putrescine stimulated the growth of some mammalian cells in tissue culture.…”
Section: Discussionmentioning
confidence: 99%